2016
DOI: 10.1186/s12913-016-1728-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of health care needs of physicians

Abstract: BackgroundThe healthcare needs of physician are not well studied.MethodsWe surveyed physicians attending a large primary care conference about their access and perceived barriers to receiving healthcare services.ResultsResponse rate was 46 % (270/592). The majority were trained in family medicine. The age category of above 60 years was the most common (39 %) and 46 % were women. Important difficulty in accessing healthcare services was reported by 39 % of physicians and the majority (61 %) reported reverting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
(18 reference statements)
4
11
0
Order By: Relevance
“…These all suggest that there would be a greater effect on the quality of services provided by those physicians, as those barriers would, in general, be likely to affect a physician's ability to provide quality care and achieve high levels of patient satisfaction. These results also similar to other study results (13). There is an urgent need for employers and policy makers to make significant changes and to increase physicians' willingness to consider their own health needs.…”
Section: Figure 2:the Usefulness Of Service To Physicians Experience supporting
confidence: 91%
See 4 more Smart Citations
“…These all suggest that there would be a greater effect on the quality of services provided by those physicians, as those barriers would, in general, be likely to affect a physician's ability to provide quality care and achieve high levels of patient satisfaction. These results also similar to other study results (13). There is an urgent need for employers and policy makers to make significant changes and to increase physicians' willingness to consider their own health needs.…”
Section: Figure 2:the Usefulness Of Service To Physicians Experience supporting
confidence: 91%
“…Difficulties in finding the time for health care were most common among those who worked more than 60 hours per week. These results support the findings of another study, which also found that those who work more than 60 hours per week were most likely to resort to selfdiagnosis/self-treatment and were most likely to have difficulties in finding the time for their own health care needs (13). These results were not unexpected, as it is clear that those who work longer hours will have less time available for seeking health care, and will, therefore, resort to self-diagnosis or self-treatment.…”
Section: Figure 2:the Usefulness Of Service To Physicians Experience supporting
confidence: 89%
See 3 more Smart Citations